High performance sub-430°C epitaxial silicon PIN selector for 3D RRAM - Mandapati, R.; Shrivastava, S.; Das, B.; Sushama, S.; Ostwal, V.; Schulze, J.; Ganguly, U. (Device Research Conference - Conference Digest, DRC, 2014)
The high performance of Si based selection devices is constrained by the high processing temperature requirement (>700°C) for 3D storage memory application. Many high performance Si based selection devices have been demonstrated. Epitaxial [1] and poly PN junction diodes [2-3] have been demonstrated for unipolar RRAM while epitaxial NPN punch-through diodes [4] has been developed for bipolar RRAM as summarized in Table 1. However, Si based selection devices require high temperature (>700°C) epitaxy, CVD, or crystallization. The main challenges for low temperature process are (i) high dopant activation for on-current density (ii) low defects for low off-current. In this paper, we demonstrate that sub-430°C temperature Si diodes by Si MBE with excellent performance. 3D stacking by various strategies e.g. lateral epitaxial overgrowth on seed hole [5], is enabled by back-end compatible temperature of epitaxy. © 2014 IEEE.
CRIS-Team Scopus Importer:2021-06-29